2008
DOI: 10.1007/s11270-008-9691-2
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficiency of the Direct Substitution Approach for Reactive Transport Problems in Porous Media

Abstract: Nonlinear reactive transport problems can be solved using the Operator Splitting (OS) approach, where transport and reaction processes are separated or the Direct Substitution Approach (DSA) where chemical and transport equations are solved simultaneously. The OS techniques can be very attractive, but are known to introduce splitting errors with SNIA (Non Iterative OS) and have low convergence rate with SIA (Iterative OS). These problems are avoided with DSA which is more robust than OS schemes. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In addition, there are very few comparisons that provide information about the performance of the numerical methods used. The literature devoted to the comparison of sequential and global approaches for T-C coupling [13,16,35,36,39,42,43] provides some discussion that is mostly qualitative in nature. Reeves and Kirkner [34] provide the computing times required for the solution of a 1D problem with sorption of one, two, or three components for a number of methods.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are very few comparisons that provide information about the performance of the numerical methods used. The literature devoted to the comparison of sequential and global approaches for T-C coupling [13,16,35,36,39,42,43] provides some discussion that is mostly qualitative in nature. Reeves and Kirkner [34] provide the computing times required for the solution of a 1D problem with sorption of one, two, or three components for a number of methods.…”
Section: Introductionmentioning
confidence: 99%
“…Since the review article of Yeh and Tripathi [28], three ways are well known for reactive transport modelling: the global approach where both transport and chemical operators are solved simultaneously [9,10,22,24]; the iterative operator splitting approach where both operators are solved separately but coupled by Picard-like iterations [5,6,14,18,26]; and the non-iterative operator splitting approach where transport and chemistry operators are separately solved only one time per time step [1,2,27]. In this work, we present the non-iterative operator splitting approach.…”
mentioning
confidence: 99%
“…1 is discretized using centered finite volumes for the spatial derivative and first-order backward Euler scheme for the time derivative, (2) The chemical Eqs. 3-8 are substituted into the discretized transport equation, and (3) The resulting system of nonlinear algebraic equations is solved iteratively with the Newton-Raphson method (Fahs et al 2008). The tolerance criterion for the convergence of the iterative process is ε STD =10 −5 .…”
Section: Time Step Management With the Standard Giamentioning
confidence: 99%
“…However, the GIA is known to be difficult to implement and requires the solution of a larger system than with the OS approach (Saaltink et al 2001). The comparison between GIA and OS approach has been largely discussed in the reactive transport literature (Yeh and Tripathi 1989;Steefel and Yabusaki 1995;Steefel and MacQuarrie 1996;Shen and Nikolaidis 1997;Saaltink et al 2001;Hammond et al 2005;Fahs et al 2008). Several recent works have shown that the GIA can be more efficient than the OS approach (Steefel and MacQuarrie 1996;Shen and Nikolaidis 1997;Saaltink et al 2001;Fahs et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation